Eksplorasi Menyelaraskan Penilaian dengan Pengajaran dan Pembelajaran Materi Kitābah di Madrasah Tsanawiyah - Nurhalimah, Lilis; Syihabuddin, Syihabuddin; Maulani, Hikmah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to align assessment in teaching and learning of the Kitabah material based on Assessment for Learning (AFL). To achieve this goal, this study employed a qualitative approach with a phenomenological design, utilizing two data sources: primary data collected through interviews and observations, and secondary data obtained from the MTs Arabic curriculum and the seventh-grade teaching modules at MTs Al-Musyawarah Lembang. The study population consisted of 26 students with 7 samples selected through purposive sampling. Data analysis included data condensation, presentation, and verification through the application of triangulation of sources and methods to ensure data validity. The results of the study indicate that assessment practices are not fully aligned with the principles of Assessment for Learning of the four main prerequisites for optimal AfL integration, only one has been implemented: teachers simplifying learning objectives according to student abilities. Other prerequisites, such as assessments, do not provide constructive feedback. Students have not been trained to assess themselves or their peers, and schools do not adequately support the learning of the kitabah material, including the provision of textbooks that are more suited to students' abilities.